Penerapan Framework COBIT dalam Meningkatkan Keamanan Data pada Sistem Informasi Pegadaian Swasta PT Budi Gadai Indonesia - Oktaviana Bangun; Fransisko; Dolly; Sarah; Reski; Dewi (Universitas Mandiri Bina Prestasi, 2026)
Safeguarding digital assets is a critical element in overseeing corporate information infrastructures, becoming vital within the financial services landscape, including private pawnshops. This research focuses on fortifying data protection at PT Budi Gadai Indonesia by adopting the performance-based COBIT 2019 system and evaluating its operational impact. Using a descriptive-qualitative methodology, the study examines security management practices and their integration with the DSS and EDM areas of the framework. Conducted as a longitudinal evaluation (2020–2025), the deployment followed a systematic multi-phase strategy. Empirical evidence indicates that integrating this governance model bolstered security through rigorous access monitoring, refined audit logs, and structured risk mitigation. Specifically, the activation of DSS05 and DSS06 protocols lowered breach vulnerabilities by 68% and ensured stricter regulatory adherence. Notably, the integrity maturity rating surged from 2.22 to 4.24, representing a 91% enhancement. These outcomes suggest that international security standards are instrumental in securing information systems within the private pawn brokerage sector.